2011
DOI: 10.1007/s00535-010-0358-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors predictive of sustained virological response following 72 weeks of combination therapy for genotype 1b hepatitis C

Abstract: Complementary statistical and data mining approaches were used to identify a subgroup of patients likely to benefit from 72 weeks of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Nonetheless, supporting this assumption is the significantly greater enrichment in gt-1 patients of both cold-precipitating material with IgM molecules showing RF activity and HCV-Cp, as in this form of MCG, the RNA-to-Cp ratio is higher. It is well known that the genetic variability of HCV affects the metabolism of infected liver cells and influences the outcome of infection [41]. In addition, the RNA chaperone activity of core protein includes genomic RNA dimerization, which may constitute the regulatory switch determining translation/replication versus replication/packaging of viral RNA [42].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, supporting this assumption is the significantly greater enrichment in gt-1 patients of both cold-precipitating material with IgM molecules showing RF activity and HCV-Cp, as in this form of MCG, the RNA-to-Cp ratio is higher. It is well known that the genetic variability of HCV affects the metabolism of infected liver cells and influences the outcome of infection [41]. In addition, the RNA chaperone activity of core protein includes genomic RNA dimerization, which may constitute the regulatory switch determining translation/replication versus replication/packaging of viral RNA [42].…”
Section: Discussionmentioning
confidence: 99%
“…In genotype 1, extending therapy improves the SVR rate in patients with delayed viral response (i.e., HCV-RNA becomes undetectable between 13 and 24 weeks after starting treatment). [14][15][16] These findings indicate that response-guided therapy is one of the most efficient methods for treatment. A recent meta-analysis showed that 72-week extended treatment improved the SVR rate in slow responders with HCV genotype 1.…”
Section: Introductionmentioning
confidence: 97%
“…[14][15][16] This is an explicit, quantitative and systematic approach, and allows clinicians to maximize the net benefit to patients. 17 Recently, a decision-tree algorithm has been used to reveal the clinical feature profiles associated with sustained virological response to antiviral therapy against HCV 18,19 and disease progression of HCC. 20 The aim of this study is to investigate dietary profiles associated with HCV-PNALT using a decision-tree algorithm.…”
Section: Introductionmentioning
confidence: 99%